Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms23137238
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a Paradigm Shift in Auger-Electron Cancer Therapy with Tumor-Specific Radiopeptides Targeting the Mitochondria and/or the Cell Nucleus

Abstract: Although 99mTc is not an ideal Auger electron (AE) emitter for Targeted Radionuclide Therapy (TRT) due to its relatively low Auger electron yield, it can be considered a readily available “model” radionuclide useful to validate the design of new classes of AE-emitting radioconjugates. With this in mind, we performed a detailed study of the radiobiological effects and mechanisms of cell death induced by the dual-targeted radioconjugates 99mTc-TPP-BBN and 99mTc-AO-BBN (TPP = triphenylphosphonium; AO = acridine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 69 publications
(175 reference statements)
0
22
0
Order By: Relevance
“…The studies with 99m Tc showed that mitochondria targeting is as effective as the nuclear targeting to induce lethal radiobiological effects in tumor cells. 24,25 Therefore, these results pinpointed that cell-specific mitochondria targeting strategies justify further attention in the design of radioconjugates for AE-RPT of cancer.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The studies with 99m Tc showed that mitochondria targeting is as effective as the nuclear targeting to induce lethal radiobiological effects in tumor cells. 24,25 Therefore, these results pinpointed that cell-specific mitochondria targeting strategies justify further attention in the design of radioconjugates for AE-RPT of cancer.…”
Section: Introductionmentioning
confidence: 91%
“…99m Tc is not an ideal AE emitter for TRT due to its relatively low Auger electron yield but can be considered a readily available “model” radionuclide, useful to “validate” the design of new classes of AE-emitting radioconjugates. The studies with 99m Tc showed that mitochondria targeting is as effective as the nuclear targeting to induce lethal radiobiological effects in tumor cells. , Therefore, these results pinpointed that cell-specific mitochondria targeting strategies justify further attention in the design of radioconjugates for AE-RPT of cancer.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Towards this goal, a variety of 99m Tc complexes carrying different structural motifs for a preferential uptake by the nucleus, such as nuclear localization sequences (NLS) or DNA intercalators, were designed and evaluated. [75][76][77][78][79][80][81][82][83][84][85][86][87] However, the development of strategies aiming at a selective and specific delivery of radiocomplexes to the nucleus of tumor cells is a quite demanding task, as shown by the results recently reported for AE-emitting 111 In-radioconjugates combining NLS sequences with target-specific biomolecules. [88] The presence of the NLS improved the nuclear uptake of the radioconjugates but this effect was accompanied by a loss of specificity towards the target tumor cells and poor biodistribution profiles due to the accumulation of activity in excretory non-target organs like the liver and the kidneys.…”
Section: M Tc-radiocomplexes For Auger Electron Therapymentioning
confidence: 99%
“…Adapted images from. [85] Figure 16. Structures of heterometallic complexes reported as potential DNA targeting agents.…”
Section: Platinum Conjugatesmentioning
confidence: 99%